PTH-297 Does height of the rectal cancer impact on the use of neo-adjuvant therapy and ultimate oncological outcomes?. (22nd June 2015) - Khan, MAS; Hakeem, AR; Scott, N; Botterill, I
Abstract : Introduction: The impact of the height of rectal cancer from the anal verge and its ultimate clinical significance is controversial 1 (as debated by Tekkis et al in their published paper). The aim of this study is to assess the influence of rectal cancer height and oncological outcomes treated in a specialised colorectal cancer unit. Method: Prospectively collected data on a patient pathway manager (PPM) for patients who underwent primary rectal cancer treatment at our unit from January 2005 till December 2010 were analysed. Low cancer was defined as tumour <5 cm from the anal verge, as assessed by endoscopy, digital rectal examination and MRI scan. Recurrent cancer, palliative resection, perforated tumours and those requiring pelvic exenteration were excluded. Chi 2 test was used for statistical analysis. Results: There were 226 male and 133 female patients with mean age of 70 years (Range: 21–93). Of the 359 rectal cancer patients, 149 (41.5%) had low and 210 (58.5%) had medium/high cancer. Outcome data of tumour height, neo-adjuvant therapy, CRM status, type and mode of surgery and disease relapse is tabulated in Table 1 . Conclusion: Height of rectal cancer does influence use of neo-adjuvant therapy and ultimate R0 resection rate. It does not influence loco-regional or systemic recurrent rates. Disclosure of interest: None Declared. Reference: Bhangu A, Rasheed S, Tekkis P, et al . Does rectal cancer height influence the oncological outcome? Colorectal Dis. 2014;16:801808